The effect of similarity between owner’s values and their perceptions of their pet’s values on life satisfaction - Sneddon, Joanne; Ye, Sheng; Lee, Julie A. (Frontiers in Psychology, 2022)
It is often assumed that pet ownership improves peoples’ wellbeing, but evidence of this pet effect has been mixed. We extended past research on pet personality, the pet effect, and value congruence to examine whether people perceive their pets to have human-like values and if owner-pet values similarity has a positive effect on owners’ life satisfaction. In a large and diverse sample of Australian dog and cat owners, we find that people imbue their dogs and cats with humanlike values in a way that reflects the theoretical circular structure of values. Importantly, perceptions of the values of dogs and cats differed in that dogs were perceived to prioritize more social-focus values, whereas cats were perceived to prioritize more personal-focus values. Additionally, we find that similarity in the values profile of dog owners and their dogs is positively associated with life satisfaction, but this was not the case for cats. However, when we examined associations between individual values similarity and life satisfaction, our results suggest a more complex and nuanced picture of both direct and indirect similarity effects.